Socialization of Education about Early Marriage in Rural Communities - Sarkar Malla (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The socialization of education concerning early marriage in rural areas is the subject of this report. In many rural areas, girls are still getting married off at young ages, which has devastating effects on their futures as learners and on their health and safety. Community workshops, peer education programs, parental education, and media campaigns are all included in the report as viable socializing activities to encourage girls to continue their education and postpone marriage. Effective tactics, such as incorporating local leaders, partnering with schools and health centers, employing culturally relevant materials, monitoring and evaluation, are needed to put these efforts into action. To guarantee the success of these endeavors, however, it will be necessary to overcome obstacles including community opposition, scarce resources, and language and cultural divides. In order to enhance results for girls, families, and communities, the report emphasizes the necessity of a long-term commitment to supporting girls' education and delaying marriage.